Data stories and cognitive load: a systematic review of the picture superiority effect - Hassan, Mohammed Rakibul; S. Abd. Aziz, Madihah; Hassan, Raini (IEEE, 2026)
This study investigates the Picture Superiority Effect (PSE) as a mechanism for enhancing data storytelling and reducing cognitive load. A systematic literature review (SLR) of 16 peer-reviewed studies published between January 2022 and June 2025 was conducted following PRISMA 2020 and CASP guidelines. Results show that visual formats such as infographics, dashboards, and data comics outperform text-only approaches, particularly when tailored to audience expertise and domain context. Relevant, well-integrated visuals improve memory retention, engagement, and comprehension, whereas irrelevant or overly complex visuals can increase cognitive load. The synthesis draws on Dual Coding Theory, Cognitive Load Theory, and Cognitive Semiotics to explain these effects. Despite growing adoption of PSE-based approaches, challenges persist in developing standardized design guidelines, accurately measuring cognitive load, and adapting visuals for diverse audiences. This review consolidates empirical evidence, identifies key research gaps, and offers design recommendations for adaptive, user-centered visual storytelling applicable to domains including education, healthcare, and governance.